Systematic Study on Genetic and Epimutational Profile of a Cohort of Amsterdam Criteria-Defined Lynch Syndrome in Singapore - Liu, Yanqun (Public Library of Science, 2014)
BACKGROUND: Germline defects of mismatch repair (MMR) genes underlie Lynch Syndrome (LS). We aimed to gain comprehensive genetic and epigenetic profiles of LS families in Singapore, which will facilitate efficient molecular diagnosis of LS in Singapore and the region. METHODS: Fifty nine unrelated families were studied. Mutations in exons, splice-site junctions and promoters of five MMR genes were scanned by high resolution melting assay followed by DNA sequencing, large fragment deletions/duplications and promoter methylation in MLH1, MSH2, MSH6 and PMS2 were evaluated by multiplex ligation-dependent probe amplification. Tumor microsatellite instability (MSI) was assessed with five mononucleotide markers and immunohistochemical staining (IHC) was also performed. RESULTS: Pathogenic defects, all confined to MLH1 and MSH2, were identified in 17 out of 59 (28.8%) families. The mutational spectrum was highly heterogeneous and 28 novel variants were identified. One recurrent mutation in MLH1 (c.793C>T) was also observed. 92.9% sensitivity for indication of germline mutations conferred by IHC surpassed 64.3% sensitivity by MSI. Furthermore, 15.6% patients with MSS tumors harbored pathogenic mutations. CONCLUSIONS: Among major ethnic groups in Singapore, all pathogenic germline defects were confined to MLH1 and MSH2. Caution should be applied when the Amsterdam criteria and consensus microsatellite marker panel recommended in the revised Bethesda guidelines are applied to the local context. We recommend a screening strategy for the local LS by starting with tumor IHC and the hotspot mutation testing at MLH1 c.793C>T followed by comprehensive mutation scanning in MLH1 and MSH2 prior to proceeding to other MMR genes.